Water remediation with a dielectric-free portable triple-electrode cold plasma discharge system - Sutjitjoon, Prathana; Nupangtha, Wasin; Saidarasamoot, Kamtorn; Locharoenrat, Kitsakorn; Lekchaum, Sarai (My University, 2024)
This paper presents the design and application of a portable multi-electrode cold plasma corona discharge system for pollutant degradation in wastewater. The system generated stable plasma without a dielectric barrier, producing active species such as hydroxyl radicals, hydrogen peroxide, nitrite, and nitrate. The experimental results presented a pollutant degradation efficiency of 100%, reducing methylene blue as a model pollutant from 6 ppm to 0 ppm within 125 s at an optimized electrode distance of 0.20 cm. This optimization minimizes the risks associated with the arcing and self-collision of plasma streams while sustaining continuous plasma discharge, ensuring the maximum breakdown voltage and high ion density for efficient plasma production. The system further demonstrated its application in treating hand washing as a target pollutant to reduce the risk of infection during the COVID-19 pandemic. A comparative analysis highlighted the advantages of the system in terms of rapid treatment, energy efficiency, and low-cost operation. The processed water met the World Health Organization (WHO) wastewater discharge standards and WHO guidelines for virus elimination, with residual nitrogen compounds maintained below 50 ppm and hydrogen peroxide levels kept under 5,000 ppm, confirming the effectiveness of the system in pathogen reduction and wastewater purification.
Keywords: ion density; Ionization; plasma generation; reactive species; wastewater treatment